2014
DOI: 10.2139/ssrn.2555172
|View full text |Cite
|
Sign up to set email alerts
|

Women as Main Earners in Europe

Abstract: This paper conducts a cross-sectional empirical research aimed at documenting that couples with women as main earners represent a non-negligible share of the European populations today. We identify the socio-demographic characteristics of couples with women as main earners in comparison to couples with men as main earners and couples with equal-earners. We undertake a comparative and cross-temporal approach using micro-level survey data for 18 European countries from the European Social Survey and two years, 2… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The results lent partial support to our expectation of decreasing traditional GRA for moves that (in part) support the career of the female partner (Hypothesis 5: Female-led or co-led mover hypothesis). This tentatively suggests that the emerging trends in female-breadwinner households in Britain (Vitali and Mendola 2014) are permeating in couple relocation's behaviour and outcomes.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 92%
“…The results lent partial support to our expectation of decreasing traditional GRA for moves that (in part) support the career of the female partner (Hypothesis 5: Female-led or co-led mover hypothesis). This tentatively suggests that the emerging trends in female-breadwinner households in Britain (Vitali and Mendola 2014) are permeating in couple relocation's behaviour and outcomes.…”
Section: Discussion and Concluding Remarksmentioning
confidence: 92%
“…Among the many resources individuals have and may share within a couple, income has been argued to be a crucial marker of power relations between partners (1997, Pahl, 1989Pahl, , 1999, and is therefore of primary interest here. Analysing households in terms of partners' share of total labour income enables us to evaluate the different (even competing) expectations of different theoretical perspectives, further accounting for qualitative differences between households where a man (or a woman) is the main breadwinner, and households where both bring in similar amounts (see also Vitali & Arpino, 2016;Vitali & Mendola, 2014).…”
Section: Research Question and Expectationsmentioning
confidence: 99%
“…We consider how different combinations of changes in working hours led to rearranging the time division of household chores. Moreover, since studies of inequalities have highlighted how the interplay of partners' resources within couples can vary (Dieckhoff, Gash, Mertens, & Romeu Gordo, 2020;Grotti & Scherer, 2016;Vitali & Arpino, 2016;Vitali & Mendola, 2014), we assess the extent to which the possible renegotiation differed depending on the partners' contributions to household labour income, distinguishing male breadwinner, female breadwinner and couples earning similar amounts.…”
Section: Introductionmentioning
confidence: 99%
“…Confronting the new household economics theory, for several decades, studies from Northern Europe have shown the compatibility between women's work and childbearing (Duvander and Andersson 2006). Educational expansion among women may result in their holding better labormarket positions and in the emergence of female-breadwinner couples (Drago et al 2005, Vitali andMendola 2014).…”
Section: Employmentmentioning
confidence: 99%